If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 111 + -9p = 12 Solving 111 + -9p = 12 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-111' to each side of the equation. 111 + -111 + -9p = 12 + -111 Combine like terms: 111 + -111 = 0 0 + -9p = 12 + -111 -9p = 12 + -111 Combine like terms: 12 + -111 = -99 -9p = -99 Divide each side by '-9'. p = 11 Simplifying p = 11
| 5(x+2)-2(x+3)=4(x+1) | | 17=39-2p | | 6=72-11q | | 5y+6y-81=7x+102+65y | | 12q+9=81 | | 8=56-4x | | 13=58-5q | | 8q-35=61 | | 21=48-9q | | 53=6p+11 | | 30-5p=5 | | 60-4x=8 | | 14=47-3x | | 75-8x=3 | | 25x^3=0 | | (3x-18)/(6x-15) | | 4x^3-28x^2+48x=4 | | -5(2t+1)=-65 | | -10(s+1)=-83 | | 16=56-8x | | 6(4s+4)=192 | | x+(x(2)+2.5)=471.8 | | 5(2l+6)=80 | | 6=30-6x | | 3a+7a-4a= | | 2(a-8)=80 | | 26=4a-22 | | 12a-25=35 | | 4(3x-1)-2x=56 | | 50=7a-6 | | 7x+1250=1264 | | 21+9a=66 |